2020
DOI: 10.1021/acscentsci.0c00587
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Nanocrystalline Cesium Lead-Halide Perovskites as Seen by Halide Magnetic Resonance

Abstract: Lead-halide perovskites increasingly mesmerize researchers because they exhibit a high degree of structural defects and dynamics yet nonetheless offer an outstanding (opto)electronic performance on par with the best examples of structurally stable and defect-free semiconductors. This highly unusual feature necessitates the adoption of an experimental and theoretical mindset and the reexamination of techniques that may be uniquely suited to understand these materials. Surprisingly, the suite of methods for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 83 publications
7
69
0
Order By: Relevance
“…We can envisage also two other possible origins of the different bands: a change in the stoichiometry of Cs, Pb, Cl [ 37 ] or different crystalline phase of CsPbCl 3 in the MCs and NC, in analogy with reports on hybrid perovskites [ 38 , 39 , 40 ]. Two recent papers [ 41 , 42 ] highlighted structural changes crossing between NC and MCs and therefore it is very likely to suppose that the different energies of the α and β bands reflect such changes. Presently, we cannot experimentally distinguish between the previous hypotheses about the origin of the β-band: however, it must be pointed out that our data clearly show the formation of extended electronic states as certified by the excitonic resonances of Figure 3 .…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…We can envisage also two other possible origins of the different bands: a change in the stoichiometry of Cs, Pb, Cl [ 37 ] or different crystalline phase of CsPbCl 3 in the MCs and NC, in analogy with reports on hybrid perovskites [ 38 , 39 , 40 ]. Two recent papers [ 41 , 42 ] highlighted structural changes crossing between NC and MCs and therefore it is very likely to suppose that the different energies of the α and β bands reflect such changes. Presently, we cannot experimentally distinguish between the previous hypotheses about the origin of the β-band: however, it must be pointed out that our data clearly show the formation of extended electronic states as certified by the excitonic resonances of Figure 3 .…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“… 14 Another example is the lead-depleted Cs 4 PbX 6 structure where the [PbX 6 ] 4 – octahedra are isolated (0D). 13 , 15 17 A third closely related nonperovskite structure that has lower Cs + content and does not contain [PbX 6 ] 4 – octahedra, CsPb 2 X 5 , can be described as layers (2D) of [Pb 2 X 5 ] ® clusters separated by Cs + ions. 13 , 15 17 Because of the large difference in the involved atoms’ electronegativities, all these cesium lead halides exhibit mixed bonding nature.…”
mentioning
confidence: 99%
“…Solid-state nuclear magnetic resonance (NMR) is playing an indispensable role in the research of perovskites due to its superb spectroscopic resolution of chemical structure for both organic and inorganic components. 3 …”
mentioning
confidence: 99%
“…The work done by Piveteau et al 3 demonstrated that the challenges of halide signals in lead halide perovskites (CsPbX 3 ) can be tackled with a versatile choice of both NMR and nuclear quadrupole resonance (NQR) ( Figure 2 ). Here, NQR is a similar technique to NMR, instead using zero magnetic field to collect the signal of quadrupolar nuclei.…”
mentioning
confidence: 99%
See 1 more Smart Citation